2016
DOI: 10.2139/ssrn.2898620
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Teaching English Literature at the University of Hail: Instructors' Perspective

Abstract: This descriptive-analytic study aimed at identifying the most significant impediments to teaching English literature from the perspective of male and female instructors at The University of Hail (UoH). The study was conducted during the first semester of the academic year 2015-16. A questionnaire was used to collect data from 10 female and 12 male instructors. Data analysis revealed that the instructors consider the students' level of language proficiency, the texts' linguistic and stylistic degree of difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Teaching and learning foreign literature could be a daunting task for both the instructors and learners (Hussein & Al-Emami, 2016). This affirms that literature teaching and learning requires a distinguishable method for it to be mastered.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Teaching and learning foreign literature could be a daunting task for both the instructors and learners (Hussein & Al-Emami, 2016). This affirms that literature teaching and learning requires a distinguishable method for it to be mastered.…”
Section: Introductionmentioning
confidence: 70%
“…This requires teachers to arm themselves with the skills needed to teach literature. The methodologies and approaches might differ from what is practiced in the language lessons because as claimed by Padurean (2015), English Literature should be approached differently since the (Chen, 2012;Hussein & Al-Emami, 2016;Muthusamy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have revealed that the Saudi EFL learners tend to avoid learning English literature for various reasons. For example, previous research indicated that second language learners were demotivated to study texts of English literature for different cultural, attitudinal, and emotional barriers (Hussein & Al-Emami, 2016). Some studies proved that EFL learners misperceived English literature as the most difficult part of their English learning with its ambivalent vocabulary, sentences, ideas, and complicated actions.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the teaching and learning of literature, one must fathom that it may pose some hindrances and obstacles to both the teachers and students. As argued by Hussein and Al-Emami (2016), teaching and learning foreign literature could be a daunting task for both the instructors and learners. From the teachers' view, hindrances may appear in the form of getting students to understand the lesson and arousing their interest in the lesson.…”
Section: Introductionmentioning
confidence: 99%
“…The methodologies and approaches might differ from what is practised in language lessons as claimed by Padurean (2015) who found that English literature should be approached differently because the language used is too complex. Having said that, teaching approaches, methods, and strategies employed by teachers in teaching literature should be suitable, varied, innovative and effective to maximise the teaching process (Chen 2012, Adelabu & Matthias 2013, Hussein & Al-Emami 2016, Muthusamy et al 2017. With the aforementioned issues and matters, this study postulates the following objectives: a.…”
Section: Introductionmentioning
confidence: 99%